Auxin and salicylic acid signalings counteract during the adaptive response to stress - Iglesias, María José (2011)
In a previous publication, we performed a phenotypic characterization of Arabidopsis auxin receptor mutants grown under oxidative and salt stresses. In particular, the double mutant for TIR1 and AFB2 receptors, tir1 afb2 displayed increased tolerance against salinity measured as germination rate, root elongation and chlorophyll content. Here, it is reported that salicylic acid (SA)-treated tir1 afb2 mutant shows enhanced transcript level of a pathogenesis related gene, PR1. In addition, SA-mediated repression of auxin signaling was also demonstrated. All these findings allow us to suggest that down-regulation of auxin signaling may be a common mechanism within the plant adaptative response against both biotic and abiotic stresses.